Social Change and Domestic Violence: Empirical Reflections on Islamic Family Law in Pekanbaru - Ismail, Muhamad; Zainal, Rusli; Netti, Misra; Faisal, Robithah Alam Hadi; Romianto, Irma (Journal of Islamic Law El Madani, 2025)
This study explores the relationship between social change and domestic violence within the framework of Islamic family law in Pekanbaru, Indonesia. Using a qualitative thematic approach, data were gathered through in-depth interviews with 12 purposively selected respondents, including domestic violence survivors, religious leaders, legal practitioners, and community mediators. The findings reveal that ongoing social transformations—such as shifting gender roles, economic stress, and the weakening of traditional family structures—contribute significantly to the complexity and prevalence of domestic violence cases. Respondents demonstrated varied understandings of Islamic family law, often influenced by cultural norms rather than textual Islamic doctrines. Thematic analysis identified three core themes: (1) dissonance between religious ideals and lived social realities, (2) limited legal literacy regarding Islamic marital obligations, and (3) tensions between local customary practices (adat) and formal Islamic legal frameworks. The study concludes that while Islamic family law offers normative guidance for a harmonious domestic life, its implementation faces socio-cultural and institutional obstacles. Enhancing community-based legal literacy and integrating Islamic legal principles into local dispute resolution mechanisms are recommended to address domestic violence more effectively amidst ongoing social change.